Pelatihan Penerapan Media Gambar Dalam Pembelajaran Menulis Bahasa Arab - Bancin, Nurazizah; Nur, Samsiah; Fazira, Nazwa (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2026)
The ability to write Arabic letters (maharah al-kitābah) is a fundamental competency for elementary-level learners. Many students face difficulties in recognizing and accurately writing hijaiyah letters due to monotonous teaching methods and limited supporting media. This community service activity aimed to enhance writing skills through the use of pictorial media with faint letters at Rumah Qur’an Amaliah, Tanjung Morawa. The activity was conducted in a single day, involving 20–30 learners, and employed a descriptive qualitative approach with observation sheets, documentation, and facilitator narrative reflections as instruments. The implementation included facilitator demonstrations of hijaiyah letter writing and exercises in tracing letters on object-themed worksheets. The results indicated improvements in letter recognition, writing skills, and student learning motivation. The pictorial media facilitated visual understanding, strengthened the association between letters and meaning, and enhanced fine motor skills, demonstrating potential for further development in creative and contextual Arabic language learning.